Burkina Faso : Sixth Review Under the Poverty Reduction and Growth Facility, and Requests for Waiver of Performance Criteria. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This paper assesses the Sixth Review Under the Poverty Reduction and Growth Facility (PRGF) and Requests for Waiver of Performance Criteria for Burkina Faso. The implementation of the PRGF-supported program remains largely satisfactory, with all but one of the quantitative benchmarks and indicators for end-March 2002 met, and all but two of the quantitative performance criteria, benchmarks, and indicators met at end-June 2002. The performance criterion on total net budget financing and the indicator on the ceiling on current government expenditure were not met at end-June.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet